Research on the Impact of Joystick Control Characteristics on Vehicle Driving Quality - Tan, Lifen; Jiang, Changhua; Wang, Chunhui; LiangLiu; Li, Huijun (Proceedings (International Conference on Intelligent Human-Machine Systems and Cybernetics), 2024)
This study mainly aims to examine the impact of different joystick control characteristics on driving control in a virtual simulation 1/6G gravity environment through the performance of subjective driving quality ratings of acceptable levels and average driving speeds. Using an within-subjects design, a total of 15 participants have completed a single joystick driving task along a designated route in a virtual simulation 1/6G gravity environment. The study aims to analyze the average driving speed and driving quality results of different control levels and control gains. The experimental results show that in the low gravity environment of virtual simulation, the control strategy combining longitudinal velocity mode and lateral steering mode achieves the highest driving quality, which is superior to the control strategy combining acceleration mode and lateral steering mode. In order to improve driving quality, taking into account the average driving speed performance, it is recommended to design the longitudinal control gain in speed mode as 0.48km/h/deg and the lateral control gain as 1.33 for the lowe speed range studied in the virtual 1/6G low gravity environment.